Neurological Practice in Canada - Jette, Nathalie; Yu, Amy Y.X.; Odier, Celine; Rivillas, Julian Alejandro; Schabas, Alice; Hill, Michael D. (Seminars in Neurology, 2025)
This article explores Canada's healthcare system, focusing on neurological care delivery and available national population-based data for research. Canada's publicly funded, provincially administered healthcare ensures universal access to medically necessary services, with provincial variations in coverage. Neurological care is predominantly hospital-centered, with support from advocacy groups promoting equity and research. In Quebec, stroke care is structured through regional service corridors, integrating telemedicine and geolocation-based transfer models to mitigate urban–rural disparities. British Columbia confronts challenges in providing neurological care to rural populations, utilizing outreach clinics, tele-neurology, and subsidized transportation. The First Nations Health Authority addresses unique healthcare access and governance needs for Indigenous populations. Canada's healthcare infrastructure supports population-level research via linked administrative and electronic health records, enabling comprehensive evaluations of healthcare utilization, outcomes, and quality metrics. Despite interprovincial differences and coverage limitations, advancements in data interoperability and standardization have propelled neurologic health services research.
Keywords: neurological care; Canada; ischemic stroke; administrative data; health services research